Integrated microbiome and metabolomics analysis reveals the alleviating effect of Pediococcus acidilactici on colitis - Wu, Lulu; Xue, Lixun; Ding, Xin; Jiang, Huyan; Zhang, Ranran; Zheng, Aifang; Zu, Yuan; Tan, Shuaishuai; Wang, Xin; Liu, Zhigang (Frontiers in Veterinary Science, 2025)
Colitis is a complicated disease caused by multiple factors, seriously threatening the host health and the development of animal husbandry. Probiotics have been demonstrate to participate in the active regulation of multiple gastrointestinal disease, gut microbiota and metabolism, but research on the efficacy of Pediococcus acidilactici isolated from dogs in alleviating colitis remains scarce. Here, we aimed to investigate the ameliorative effects of Pediococcus acidilactici isolated from dogs on colitis induced by LPS and its underlying molecular mechanisms. For this purpose, we collected colon contents from 15 mice for amplicon sequencing and metabolic analysis. Results showed that Pediococcus acidilactici could relieve the colon damage and cytokine disorder caused by colitis. Microbiome analysis showed that colitis could cause a significant decrease in the gut microbial diversity and abundance, but Pediococcus acidilactici administration could restore the microbial index to the control level. Metabolomics analysis showed that 8 metabolic pathways and 5 (spermine, L-Arginine, 15-Deoxy-Delta12,14-PGJ2, prostaglandin J2, and 15(S)-HETE) metabolites may be involved in the alleviation of colitis by Pediococcus acidilactici. In summary, these findings demonstrated that the positive regulation effect of Pediococcus acidilactici on gut microbiota and metabolism may be one of its underlying mechanisms to alleviate colitis. Additionally, this study also conveyed a vital message that Pediococcus acidilactici isolated from dogs may serve as a promising candidate to ameliorate Pediococcus acidilactici.